An integrated metagenomic/metaproteomic investigation of microbiota in dajiang-meju, a traditional fermented soybean product in Northeast China. (January 2019) - Xie, Mengxi; Wu, Junrui; An, Feiyu; Yue, Xiqing; Tao, Dongbing; Wu, Rina; Lee, Yuankun
Abstract: Dajiang-meju have been used as major ingredients for the preparation of traditional spontaneously fermented soybean paste in Northeast China. In this work, we sequenced and analyzed the metagenome of 12 dajiang-meju samples. To complement the metagenome analysis, we analyzed the taxonomic and functional diversity of the microbiota by metaproteomics (LC-MS/MS). The analysis of metagenomic data revealed that the communities were primarily dominated by Enterobacter, Enterococcus, Leuconostoc, Lactobacillus, Citrobacter and Leclercia . Moreover, changes in the functional levels were monitored, and metaproteomic analysis revealed that most of the proteins were mainly expressed by members of Rhizopus, Penicillium and Geotrichum . The number of sequences allocated to fungi in the fermentation process decreased, whereas the number of sequences assigned to bacteria increased with time of fermentation. In addition, functional metagenomic profiling indicated that a series of sequences related to carbohydrates and amino acids metabolism were enriched. Additionally, enzymes associated with glycolysis metabolic pathways were presumed to contribute to the generation of flavor in dajiang-meju. Proteins from different dajiang-meju samples involved in global and overview maps, carbohydrate metabolism, nucleic acid metabolism and energy metabolism were differentially expressed. This information improves the understanding of microbial metabolic patterns with respect to the metaproteomes of dajiang-meju and provides a powerful tool for studying the fermentation process of soybean products. Highlights: The study investigated the microbial community and microbial-derived proteins associated with the natural fermentation of dajiang-meju by metagenomic and metaproteomic. It revealed that the proteins related to carbohydrate and amino acid metabolisms were enriched and presumed to contribute to the generation of sensory in dajiang-meju. The prevalent microbial proteins in dajiang-meju were of fungal and bacterial origin, mainly expressed by members of Rhizopus and Penicillium .